2018
DOI: 10.5897/ajmr2018.8801
|View full text |Cite
|
Sign up to set email alerts
|

Potassium phosphite reduction of Candidatus Liberibacter spp. population on leaves of Ponkan tangerines tree with huanglongbing

Abstract: The objective of this work was to evaluate the population variation dynamics of Candidatus Liberibacter spp. under phosphite applications. The 'Ponkan' tangerines (Citrus reticulata Blanco cv. Ponkan) with symptoms and a high degree of huanglongbing (HLB) severity were used for the test. 'Ponkan' tangerine plants were treated with potassium phosphite leaf applications at a dose of 2.5 L ha-1. Applications frequency was intervals of 25 days with a total of two applications. There was variation in bacterium Cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…On the contrary, in other investigations, it has been observed that Citrus sinensis cv. Navelina has a higher Ca content when infected with HLB [48]. The literature mentions that citrus fruits infected with HLB can present Ca deficiencies because bacteria use this mineral for their growth [49].…”
Section: Mineral Content Of Citrus Limon and Citrus Sinensismentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, in other investigations, it has been observed that Citrus sinensis cv. Navelina has a higher Ca content when infected with HLB [48]. The literature mentions that citrus fruits infected with HLB can present Ca deficiencies because bacteria use this mineral for their growth [49].…”
Section: Mineral Content Of Citrus Limon and Citrus Sinensismentioning
confidence: 99%
“…This mechanism occurs across the plasma membrane via permeable ion channels [39]. In addition, calcium strengthens cell walls and provides greater protection against pathogens, which is one of the reasons why symptomatic fruits with HLB are harder and have a thicker shell [48,52].…”
Section: Mineral Content Of Citrus Limon and Citrus Sinensismentioning
confidence: 99%
“…KP values resulted significantly higher than those of the untreated trees, while no relevant differences were found in comparison with G, which, in turn, presented significant differences with T only for LAD values and only at a 95% confidence level. The behavior of the trees treated with potassium phosphite alone can be traced back to its booster effect on plant growth, even if antibacterial effects on populations of Candidatus liberibacter [ 76 ] and Streptomyces scabies [ 77 ] have been described. The percentage increase varied from 20.19 (PE3), to 10.77 (KP), to 6.72 (G), to 2.46% (T) for LAI and from 9.25 (PE3), to 8.29 (KP), to 6.51 (G), to 0.26% (T) for LAD.…”
Section: Resultsmentioning
confidence: 99%